Directive Speech Act Realization In The Teaching And Learningat Magister Of Language Studies Muhammadiyah University Of Surakarta 2014 - Tamara, Chintya Widi; , Agus Wijayanto, Ph.D; , Dr. Anam Sutopo, M.Hum (2015)
The study investigated the realization of directive speech act conducted by the lecturer and students in the teaching and learning at magister of language studies Muhammadiyah University of Surakarta relating to different gender and politeness strategy. The data elicited, using observation and documentation by video recorder, from 22 students and 6 lecturers. The observation has been conducted from 28 October 2014 to 17Mei 2014. There are totally 371 minutes and 33 second of voice recording from. The collected data are analyzed by using in Austin's schema, Searle (1977)'s theory of directive speech acts, Brown and Levinson's theory of politeness strategy. The finding of the research are described in line with the problem statement as follows: first, Based on the previous analysis, the finding of the whole data can be summarized in the following description. The writer found 28 data which show descriptive speech acts. In language form or sentence types of directive speech acts, the result of this study show that there are 40 data (36%) categorized as commanding acts, 16 data (14%) categorized as request acts, 4 data (3%) categorized as admonishing act, 20 data (18%) categorized as suggesting acts, 12 data (11%) categorized as urging acts, 12 data (11%) categorized as reminding acts, and 8 data (7%) categorized as reproving acts. There is no data (0%) that categorized as ordering, advising, warning, prohibition, and inviting. Second, The finding research of female utterances show that almost female express direct utterances in the dialog using commanding in every situation. Third,The most data of directive speech acts were delivered by lecturer that uses commanding utterances and For the student, requesting, suggesting, and reminding utterances use in the dialog. The student choose that utterances in the form of politeness attitude when the students ask to the lecturer or the other students. The last,Based on the finding, it can be seen that there is relationship between directive speech act, the utterances said by female and male, the utterances said by lecturer and students, politeness strategies. if the speaker is a lecturer that ask something about what should to do, he/she can use an imperative form functioning as commanding and applies the bald on record as his/her politeness strategy. The relationship between directive speech acts, the utterances said by female and male, the utterances said by lecturer and students, politeness strategies. Key word : Directive Speech Act, Politeness strategy, Gender